2003
DOI: 10.1073/pnas.0237335100
|View full text |Cite
|
Sign up to set email alerts
|

Interstice mutations that block site-to-site translocation of a misactivated amino acid bound to a class I tRNA synthetase

Abstract: Class I aminoacyl-tRNA synthetases catalyze editing reactions that prevent ambiguity from entering the genetic code. Misactivated amino acids are translocated in cis from the active site for aminoacylation to the center for editing, located Ϸ30 Å away. Mutational analysis has functionally separated the two sites by creating mutations that disrupt the catalytic center for editing but not for aminoacylation and vice versa. What is not known is whether translocation per se can be disrupted without an effect on ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 42 publications
(86 reference statements)
0
21
0
Order By: Relevance
“…The proposed model for pre-transfer editing by IleRS (and perhaps other class I tRNA synthetases) is highly complex (53,54). Pre-transfer editing is initiated with a "priming" step, whereby the misactivated amino acid is first covalently attached to tRNA and then shifted to the remote editing site.…”
Section: ϫ3mentioning
confidence: 99%
“…The proposed model for pre-transfer editing by IleRS (and perhaps other class I tRNA synthetases) is highly complex (53,54). Pre-transfer editing is initiated with a "priming" step, whereby the misactivated amino acid is first covalently attached to tRNA and then shifted to the remote editing site.…”
Section: ϫ3mentioning
confidence: 99%
“…Studies with the class Ia synthetases IleRS (Schmidt and Schimmel 1994;, valyl-tRNA synthetase (ValRS; , and LeuRS (Chen et al 2000;Cusack et al 2000;Mursinna et al 2001) showed that the aminoacylation and editing active sites of these enzymes are spatially separate; an ∼200-amino-acid insert in the aminoacylation site, designated CP1, is responsible for the editing activity (Schmidt and Schimmel 1995;Nureki et al 1998;Fukai et al 2000Fukai et al , 2003Lincecum et al 2003). Cognate tRNAs specifically trigger transfer of misactivated amino acids from the synthetic active site to the editing active site, accounting for the tRNA dependence of the editing reaction (Silvian et al 1999;Fukai et al 2000;Bishop et al 2002Bishop et al , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, this activity seems to be enhanced in the presence of tRNA (20,21,23). Thus, in the evolution of LeuRS, IleRS, and ValRS, the original insertion of the CP1 domain likely affected fidelity via a set of mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Both tRNA-dependent (20)(21)(22)(23) and tRNA-independent (22, 24) pretransfer editing activities have been reported. Also, clearance of the adenylate by selective ejection from the enzyme's active site into the aqueous environment has been suggested (24).…”
mentioning
confidence: 99%